Ammonia-selective recovery from anaerobic digestate using electrochemical ammonia stripping combined with electrodialysis - Aung, Shine Lin; Choi, Jihyeok; Cha, Ho Young; Gaeun Woo; Song, Kyung Guen (Elsevier BV, 2024)
An electrodialysis (ED)-electrochemical ammonia stripping (EAS) hybrid process is used for the quick and efficient recovery of ammonia from anaerobic digestate. A series of EAS experiments using synthetic ammonia solutions was conducted to determine the optimal operating conditions for the ED-EAS hybrid process with actual anaerobic digestate. These parameters included the feeding modes (anodic vs. cathodic), applied currents, anolyte composition, and capture chemicals, with a focus on their impact on ammonia recovery. As a result, cathodic feeding showed advantages over anodic feeding because of its benefit in converting NH4+ to NH3 through successful pH elevation in the cathode compartment. High current density provided sufficient OH？ to increase the cathode compartment's pH, and using Na2HPO4, a salt of triprotic acid, as an anolyte resulted in a rapid pH increase due to pH buffering, resulting in a better ammonia recovery. Through three cycles of ED operation (8 h), the ED-EAS hybrid process experiment for actual anaerobic digestate concentrated ammonia to 3.775 g/L, three times higher than the initial concentration. Ammonia was recovered to 90.5 ± 0.4 % with 11.6 kWh/kg-NH3 energy consumption from the ED concentrate in 5 h using the EAS. This study demonstrated the possibility of ammonia-selective recovery from anaerobic digestate using an integrated ED-EAS system.